A aplicação de decisões estruturantes nas ações relativas a interesses transindividuais - Verdi, Pedro Garcia (2016)
This work starts from the idea that jurisdiction, while state power, needs to adapt to the complexity of new rights and new forms of existing dispute nowadays. Its scope study the applicability of the North American Institute of structural injunction as a way to give greater effect to the guardianships of transindividual rights. For this it was decided, first, to trace an evolutionary line of the judicial function and the civil process in order to understand the stage it is in and how emerge collective rights, as well as pave the way for understanding the opening to a collective guardianship system. Overcome this first part, which aims to introduce the reader in the scenario where the theme works part to the analysis of collective guardianships, its appearance and its relevance in the current legal system. In parallel, in order to understand the performance of today's jurisdiction, it is studied under the title of "judge's powers" the development of judicial activity from the stage where there was a judge "mouth of the law" to the current system where meets to judge more than simply applying the law, but an intellectual exercise and interpretive activity, making it the creator of the law. Finally, we study the Institute of structural injunction, from its conception in the American law, to propose the applicability in brazilian law, which is based on the analysis of concrete cases.